Food availability and security. - Gordon, Ronald M. (1992)
Argues that countries must endeavour to increase food production and productivity through the application of technologies which utilize the rural labour force and by so doing, enhances its purchasing power, resulting in a greater ability to purchase required food supplies. This would result in greater food security.